GAYA ART NOUVEAU SEBAGAI INSPIRASI DALAM PERANCANGAN DESAIN PRODUK - Devanny Gumulya; Richard Santio (Jurnal Dimensi Seni Rupa dan Desain, 2014)
AbstractArt Nouveau is an art movement originated from France. The word "Art Nouveau" in French means "New Art". Art Nouveau reached its peak popularity in the early 20th century. Art Nouveau brought "Back to Nature" theme. Therefore, the Art Nouveau lines and shapes are not far from natural lifeincluding plants and animals. In our country Indonesia, The Art Nouveau is not as popular as The Art Deco, one of the factors because the country of Indonesia is an ex Dutch colony country. Buildings built by Dutch architect were Art Deco style buildings. On the other hand there is an increase of market interest in classic contemporary interior. PT. Dempsey Nusantara is one ofexample of furniture manufacture with classic contemporary style. In this paper we try understand the design spirit of Art Nouveau from the definition, character, and its application in many countries. After understanding the thinking and visual character of Art Nouveau, it is used as an inspiration fordesigning dining set as an apprentice project in Dempsey.AbstrakArt Nouveau merupakan gerakan seni yang berasal dari Perancis. Kata “Art Nouveau” sendiri dalam bahasa Perancis berarti “Seni Baru”. Art Nouveau mencapai puncak popularitas pada awal abad 20. Seni Art Nouveau membawa tema “Kembali ke Alam”. Maka dari itu, tarikan garis dan bentuk Art Nouveau diambil dari alam meliputi flora dan fauna. Di Indonesia sendiri, Seni Art Nouveau tidaklah sepopuler Seni Art Deco. Salah satu faktor adalah karena negara Indonesia merupakan negara jajahan Belanda dimana bangunan-bangunan yang didirikanarsitek Belanda bergaya Art Deco. Disisi lain ada peningkatan minat pasar pada interior klasik kontemporer salah satu produsen adalah PT. Dempsey Nusantara. Di makalah ini kami mencoba membahas apa yang menjadi semangat desain Art Nouveau ini mulai dari definisi, karakter, dan aplikasinya di berbagai negara. Karena dengan memahami, barulah bisa dijadikan inspirasi untuk merancang set furnitur ruang makan sebagai proyek magang di Dempsey.